2017
DOI: 10.1097/ajp.0000000000000481
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence in Child and Adolescent Chronic Migraine Patients

Abstract: Objectives To examine treatment adherence among children and adolescents with chronic migraine who volunteered to be in a clinical trial using three measures: treatment session attendance, therapy homework completion, and preventive medication use via daily diary. Methods Analyses are secondary from a trial of 135 youth aged 10 to 17 years diagnosed with chronic migraine and with a Pediatric Migraine Disability score over 20. Participants were randomly assigned to cognitive behavioral therapy plus amitriptyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Adherence in this particular study was maximized with instructional handouts and three monthly phone contacts. In a pediatric study evaluating CBT and amitriptyline versus headache education with amitriptyline alone, adherence was evaluated with (1) a daily headache diary and (2) attendance at an in-person CBT session [20••].…”
Section: Behavioral Therapy Adherence In Headache Researchmentioning
confidence: 99%
“…Adherence in this particular study was maximized with instructional handouts and three monthly phone contacts. In a pediatric study evaluating CBT and amitriptyline versus headache education with amitriptyline alone, adherence was evaluated with (1) a daily headache diary and (2) attendance at an in-person CBT session [20••].…”
Section: Behavioral Therapy Adherence In Headache Researchmentioning
confidence: 99%
“…There are 3 main possible reasons for drop-outs: (1) some patients, who had improved, did not return to the control visit, (2) other patients, in whom the treatment had not worked, referred to other centers, and (3) adverse events related to drugs. An emerging literature demonstrates that patients with migraine and other headaches hesitate to adhere to pharmacological regimens ( 25 , 26 ). The lack of adherence to preventive therapies has significant consequences on disease severity, frequency of the attacks and social economics costs.…”
Section: Discussionmentioning
confidence: 99%
“…Kroon Van Diest et al [61], based on a randomized study, demonstrated the importance of Cognitive Behavioral Therapy (CBT) for adherence to pharmacological treatment and institution of lifestyle changes [62]. CBT aims, through interventions guided by a psychologist, to promote the patient's active learning in order to implement skills to deal with migraine and related conditions and situations to her.…”
Section: General and Supportive Measuresmentioning
confidence: 99%
“…Thus, during the sessions, behavioral coping skills are worked out, such as problemsolving and thought restructuring, that is, the adolescent is urged to change their ideas, beliefs, and attitudes regarding his chronic condition [62]. CBT, in combination with amitriptyline, is suggested as a first-line treatment in the context of CM in adolescents [61].…”
Section: General and Supportive Measuresmentioning
confidence: 99%